Detection of low-level animal-to-animal transmission in BALB/c mouse models of melioidosis - Klimko, Christopher P.; Barnes, Kay B.; Rill, Nathaniel O.; Shoe, Jennifer L.; Dankmeyer, Jennifer L.; Hunter, Melissa; Welkos, Susan L.; DeShazer, David; Biryukov, Sergei S.; Harding, Sarah V.; Cote, Christopher K. (Frontiers in Bacteriology, 2023)
Burkholderia pseudomallei, the causative agent of melioidosis, has two phases of infection. The acute phase occurs shortly after infection and is associated with bacterial sepsis, potentially leading to death, whilst the chronic phase occurs when infection persists for longer periods or is asymptomatic for months or years. BALB/c mice are more susceptible to melioidosis compared to C57BL/6 mice and are routinely models for the acute phase of infection. However, in some instances when medical countermeasures are being evaluated, mice continue to succumb to disease throughout the course of the experimental infection. Whilst B. pseudomallei is not known to be transmitted from mouse-to-mouse, we hypothesized that mice that have recovered from infection after medical countermeasure intervention may become reinfected from chronically infected mice. We tested this hypothesis by cohousing naïve mice with mice exposed to B. pseudomallei by the inhalational or intraperitoneal routes in either static or ventilated caging.Mice that were exposed to aerosolized B. pseudomallei transmitted the bacterium to approximately 4% of their naïve cagemates, whereas mice that were infected by the intraperitoneal route transmitted to approximately 8% of their naïve cagemates. Whilst the exact route of transmission remains to be determined, the results of this study showed that low levels of mouse-to-mouse transmission of B. pseudomallei are possible. We conclude that although the chance of reinfection is low amongst mice housed in the same cage, this possible scenario should be considered when interpreting data from the BALB/c mouse model of melioidosis in lengthy studies.